2014
DOI: 10.1016/j.bbrc.2014.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Secreted meningeal chemokines, but not VEGFA, modulate the migratory properties of medulloblastoma cells

Abstract: Leptomeningeal metastasis is a cause of morbidity and mortality in medulloblastoma, but the understanding of molecular mechanisms driving this process is nascent. In this study, we examined the secretory chemokine profile of medulloblastoma cells (DAOY) and a meningothelial cell line (BMEN1). Conditioned media (CM) of meningothelial cells increased adhesion, spreading and migration of medulloblastoma. VEGFA was identified at elevated levels in the CM from BMEN1 cells (as compared to DAOY CM); however, recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A number of studies reveal the elevated levels of VEGF-A and VEGFR2 in medulloblastoma of human patients [ 45 , 46 ]. Recent studies also show that medulloblastoma cells express both VEGF-A and VEGFR2 [ 22 , 47 ]. Nevertheless, the role of VEGF-A that plays in medulloblastoma remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies reveal the elevated levels of VEGF-A and VEGFR2 in medulloblastoma of human patients [ 45 , 46 ]. Recent studies also show that medulloblastoma cells express both VEGF-A and VEGFR2 [ 22 , 47 ]. Nevertheless, the role of VEGF-A that plays in medulloblastoma remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that VEGF-A promotes medulloblastoma cell growth via VEGFR2 signaling [ 22 ]. Other studies, however, showed that VEGF-A has no effect on medulloblastoma cell migration and invasion [ 47 , 48 ]. Using two medulloblastoma cell lines, Daoy and UW228, we demonstrated that these cell lines expressed both VEGF-A and VEGFR2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ventricular RG cells receive contact-mediated (i.e., α1/α4 laminins with β1 integrins) and diffusible signals from the meninges, and the absence of these interactions has been shown to decrease the cortical size and to enhance RG cell apoptosis ( Radakovits and others 2009 ). Meninges secreted factors have also been shown in vitro to favor proliferation and differentiation of NSCs as well as of neural cancer cells, including medulloblastoma and glioblastoma cells ( Davare and others 2014 ). Meninges exert direct effects on RG cells also by secreting high levels of retinoic acid, which triggers the switch of RG proliferation pattern from self-renewing to neurogenic divisions, thus regulating cortical neuron generation and anterior hindbrain development ( Siegenthaler and others 2009 ).…”
Section: Meninges: a Widespread Niche For Neural Progenitorsmentioning
confidence: 99%
“…Recently, our knowledge of the involvement of the meninges in the regulation of brain function has expanded. Meninges secrete signaling molecules required for neural progenitor migration and maturation ( Barber and others 2018 ; Borrell and Marin 2006 ; Choe and others 2012 ; Davare and others 2014 ; Fayein and others 1992 ; Hayashi and others 2008 ; Lehtinen and others 2011 ; Raballo and others 2000 ; Radakovits and others 2009 ; Reiss and others 2002 ). They are also involved in the control of the cerebrospinal fluid (CSF) dynamics ( Louveau and others 2017 ); in fact, a glymphatic flux of CSF has been shown to continuously flow from the perivascular space, which is formed by extroflession of the pia mater, to the neural tissue thus clearing metabolites, including Aβ products, from the brain extracellular space ( Iliff and others 2012 ).…”
Section: Introductionmentioning
confidence: 99%